Self-Confidence and Environmental Learning Adjustment among Secondary Level Students of Private and Public Sector in Punjab, Pakistan - Abid Masood Khan; Shehzad; Sumera Bano (JCTE, 2024)
The study attempted to explore the level of Self-Confidence and Environmental Learning Adjustment among the students in private and public sector schools at Secondary Level in Punjab, Pakistan. Secondary level students of District Jhang were the population of the study, and a convenient sampling technique was used for sample selection. Sample of the present study was N= 100 (n=50 students from the private sector and n=50 from the government sector. A 5-Point Likert scale questionnaire was used for data collection. After analyzing data through SPSS, ANOVA statistics showed a significant difference in the level of Self-Confidence and environmental learning adjustment among the secondary level students in the private and public sector. It can be accomplished that the different categories of school can affect the Self-Confidence and environmental learning adjustment level of students at secondary level. Tstatistics showed that the private schools’ students had more selfconfidence as compared to government schools’ students. Study findings also declared that students of private schools had more done their homework on daily basis; they make interaction with their peer group for learning problems, while they felt lonely and wished for company of their class fellows, felt bored in free time and made an effort to keep in touch with teachers as compared to government schools’ students. It was recommended on the basis of conclusion that the administration of the government education department should arrange refresher courses for the teachers and students. The present study focused on the secondary level; similar study may be carried out in other levels of students.